2020
DOI: 10.1088/1361-6528/ab8c09
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial temperature modelling for understanding pulsed laser induced solution based nanomanufacturing

Abstract: Recently, pulsed lasers have demonstrated great potential in targeted synthesis in solution based nanomanufacturing, realizing high precision and accuracy in space, time and energy input. The unique temperature history induced by pulsed lasers is indispensable to understand the related fundamentals and to realize the precision control of deposition. In this study a heat transfer model was developed and applied to predict the temporal evolution and the spatial distribution of pulsed laser induced temperature ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It was reported that a single laser pulse with proper energy could initiate and control the pathway of the nucleation of hematite nanocrystals [14]. During crystal growth, the peak power, average power, irradiation time, and so on will affect the morphology of deposited ZnO crystals [15]. However, it is still challenging to precisely manipulate heat and mass transfer only through experiments [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a single laser pulse with proper energy could initiate and control the pathway of the nucleation of hematite nanocrystals [14]. During crystal growth, the peak power, average power, irradiation time, and so on will affect the morphology of deposited ZnO crystals [15]. However, it is still challenging to precisely manipulate heat and mass transfer only through experiments [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) is one of the most common oxides that could be easily produced by hydrothermal reaction. In this work, ZnO as a vehicle for the study of crystallization was produced by the pulsed laser method. The pulsed laser as a new tool to study the crystallization , could “freeze” the crystallization process in a stepwise manner. For example, the nucleation could be initiated by a single laser pulse, and the following aging processes, such as recrystallization or dissolution–reprecipitation, could be inhibited after the single pulse .…”
Section: Introductionmentioning
confidence: 99%